Self-propagating miniature device based on shape memory alloy. (17th January 2018) - Avraham, Dekel; Faran, Eilon; Shilo, Doron
Abstract: The development of novel locomotion mechanisms is beneficial for advancing the field of self-propagating devices, which are implemented in various civilian and military applications. In this work, we present a purely mechanic, mm-sized autonomous device capable of linear propagation on a smooth, relatively flat surface. The locomotion mechanism is driven by a shape memory alloy (SMA) wire that is connected to a metallic, ring-shaped, bias spring. Periodic changes in the temperature in the vicinity of the device activate the SMA wire, and result in alternating contraction-elongation deformations of the SMA-bias spring assembly. These deformations are transferred to a linear back and forth motion of small legs that are attached at the bottom of the ring. To generate locomotion, the general conditions for obtaining asymmetric friction between needle shaped legs and a smooth surface were formulated and validated experimentally. The structure and performance of the device are modeled analytically leading to basic design rules that are validated experimentally by real-time optical tracking of the device's displacements and propagation. In addition, the potential of miniaturization of the presented locomotion concept down to the micro-meter scale is demonstrated.